A case of enteropathy-associated T-cell lymphoma (Type I) arising in stomach without refractory celiac disease - Wang Liang; Liu Yang; Lin Xu-Yong; Yu Juan-Han; Miao Yuan; Qiu Xue-shan; Wang En-Hua (BMC, 2012)
Abstract Enteropathy-associated T-cell lymphoma (EATL) is a rare peripheral T-cell lymphoma which was classified into 2 types based on histology. EATL is often, but not always, associated with celiac disease. EATL type I is a large cell lymphoma which is more common in frequency and highly associated with celiac disease compared with type II. Jejunum and ileum are the common sites, although EATL can rarely occur in the duodenum, stomach and colon or outside the gastrointestinal tract. We herein presented one case of gastric EATL, which happened in a 73-year-old Chinese male patient. Histologically, the tumor was composed of polymorphic (pleomorphic, anaplastic, immunoblastic) lymphoid cells and numerous inflammatory cells, including histiocytes, neutrophils and eosnophils in the background. The pleomorphic lymphoid cells were diffuse and strongly positive for CD3 and partially positive for CD30, while negative for CD4, CD5, CD8 or CD56. The gastric EATL should be distinguished from other gastric lesions, such as peptic ulcer, poorly-differentiated adenocarcinoma and other types of lymphoma. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1174320824810970